Grounding Critical Communication Studies - Fuchs, Christian (International communication. Four-Volume Set. Volume 2)

New Marxian Times! Reflections on the 4th ICTs and Society Conference "Critique, Democracy and Philosophy in 21st Century Information Society. Towards Critical Theories of Social Media" - Fuchs, Christian (tripleC - Journal for a Global Sustainable Information Society)

Report on Theoretical Frameworks and Previous Empirical Research. Deliverable D1.1 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Amicelle, Anthony; Bus, Jacques; El-Baba, Taghrid; Fuchs, Christian; Mordini, Emilio; Rebera, Andrew; Robinson, Neil; Trottier, Daniel; Venier, Silvia; Wright, Steve

Societal Impact Report. Deliverable D1.4 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Mordini, Emilio; Bus, Jacques; Rebera, Andrew P.; Venier, Silvia; McCarthy, Sadhbh; Hayes, Ben; Wright, Steve; Deering, Daniel; Fuchs, Christian; Trottier, Daniel; Krieglsteiner, Susann; El-Baba, Taghrid

NO2 Sensors with Reduced Power Consumption Based on Mesoporous Indium Oxide - Donato, Nicola; Wagner, Thorsten; Tiemann, Michael; Waitz, Thomas; Kohl, Claus-Dieter; Latino, Mariangela; Neri, Giovanni; Spadaro, Donatella; Malagù, Cesare (Lecture Notes in Electrical Engineering)
We report on sensing properties of ordered mesoporous nanostructures of In2O3 synthesized by nanocasting procedure towards NO2. The nanostructured material shows improved recover times and higher responses compared to non nanostructured material at low operating temperatures (100–150°C) thus allowing the use for low power NO2 sensors. These properties may be related to fast oxygen in and out propagation facilitated by an enhanced surface accessibility of the nanostructure.

Research Design & Data Analysis, Presentation, and Interpretation: Part One - Allmer, Thomas

Towards a Critical Theory of Surveillance in Informational Capitalism - Allmer, Thomas

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Weltliche deutsche Lieder in Messvertonungen des 15. und 16. Jahrhunderts. Eine erste Annäherung an das Repertoire - Höink, Dominik (Polyphone Messen im 15. und 16. Jahrhundert. Funktion, Kontext, Symbol)

Excitonic Eigenstates of Disordered Semiconductor Quantum Wires: Adaptive Wavelet Computation of Eigenvalues for the Electron-Hole Schrödinger Equation - Meier, Torsten; Mollet, Christian; Kunoth, Angela (Communications in Computational Physics)
A novel adaptive approach to compute the eigenenergies and eigenfunctions of the two-particle (electron-hole) Schrödinger equation including Coulomb attraction is presented. As an example, we analyze the energetically lowest exciton state of a thin one-dimensional semiconductor quantum wire in the presence of disorder which arises from the non-smooth interface between the wire and surrounding material. The eigenvalues of the corresponding Schrödinger equation, i.e., the one-dimensional exciton Wannier equation with disorder, correspond to the energies of excitons in the quantum wire. The wavefunctions, in turn, provide information on the optical properties of the wire. We reformulate the problem of two interacting particles that both can move in one dimension as a stationary eigenvalue problem with two spacial dimensions in an appropriate weak form whose bilinear form is arranged to be symmetric, continuous, and coercive. The disorder of the wire is modelled by adding a potential in the Hamiltonian which is generated by normally distributed random numbers. The numerical solution of this problem is based on adaptive wavelets. Our scheme allows for a convergence proof of the resulting scheme together with complexity estimates. Numerical examples demonstrate the behavior of the smallest eigenvalue, the ground state energies of the exciton, together with the eigenstates depending on the strength and spatial correlation of disorder.

Freiheit Macht Spaß. Zur Gouvernementaliät des Vergnügens - Hälterlein, Jens (Die vergnügte Gesellschaft. Ernsthafte Perspektiven auf modernes Amüsement)

Die Kritik der Konsumgesellschaft und die Praxis des Konsums - Hälterlein, Jens (Transnationale Vergesellschaftung. Verhandlungen des 35. Kongresses der Deutschen Gesellschaft für Soziologie in Frankfurt am Main 2010)

A normal form for definite quadratic forms over $\mathbb{F}_{q}[t]$ - Kirschmer, Markus (Mathematics of Computation)
An efficient algorithm to compute automorphism groups and isometries of definite Fq[t]-lattices for odd q is presented. The algorithm requires several square root computations in Fq₂ but no enumeration of orbits having more than eight elements.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Kirchentage, Festivals, Conventions - Religiöse Happenings als Orte der Glaubensbildung - Schroeter-Wittke, Harald (Glaubensbildung. Die Weitergabe des Glaubens im europäischen Protestantismus. Formaton of Faith. Handing down Faith in European Protestantism)

Kirchentags, Festivals, Conventions - Religious Happenings as Places for the Formation of Faith - Schroeter-Wittke, Harald (Glaubensbildung. Die Weitergabe des Glaubens im europäischen Protestantismus. Formaton of Faith. Handing down Faith in European Protestantism)

Chronikbücher - ein religionspädagogischer Kommentar in der Bibel - Schroeter-Wittke, Harald (Religionspädagogischer Kommentar zur Bibel)

Auf die Plätze - Sorgen - Los. Bibelarbeit auf dem Wege zu Mt 6,19-34 (BAB_093_0140) - Schroeter-Wittke, Harald; Keuchen, Marion; Leutzsch, Martin; Weßler, Sarah-Luise (Dokumente CD-ROM des 33. DEKT Dresden 2011)

Muss die Freiheit wohl grenzenlos sein? Statement beim Feierabendmahl "Freiheit aufgetischt" am Zwinger (FRE_002_0181) - Schroeter-Wittke, Harald (Dokumente CD-ROM des 33. DEKT Dresden 2011)

Religion als Thema der Unterhaltung im populären Spielfilm - Schroeter-Wittke, Harald (Handbuch Theologie und Populärer Film Band 3)

Liebe und Sexualität - Schroeter-Wittke, Harald (Evangelischer Taschenkatechismus)

Religionspädagogischer Kommentar zur Bibel

Ingolf U. Dalferth / Stefan Berg (Hg.): Gestalteter Klang - gestalteter Sinn. Orientierungsstrategien in Musik und Religion im Wandel der Zeit, Leipzig 2011 - Schroeter-Wittke, Harald (Theologische Revue)

Transmission und Eventuelle Kirche. Beobachtungen zu Kirchen-, Katholiken- und Weltjugendtagen zwischen Religion und Gesellschaft - Schroeter-Wittke, Harald (Zeitschrift für Theologie und Gemeinde)

Christoph Stange: Zum Umgang mit Religiöser Musik aus musikpädagogischer Sicht, Essen 2011 - Schroeter-Wittke, Harald (Theologische Literaturzeitung)

Schwebende Verfahren. Zur performativen Dimension der Seelsorge - Schroeter-Wittke, Harald (Wege zum Menschen)

If on a Winter's Night... Stings Weihnachtswahrnehmungen - Schroeter-Wittke, Harald (Praktische Theologie)

Presshärten von Rohren und Profilen mittels formlos festen Stoffen - Tekkaya, A. Erman; Mennecart, Thomas; Witulski, Jörg; Homberg, Werner; Rostek, Tim

Introduction: Marx is Back – The Importance of Marxist Theory and Research for Critical Communication Studies Today - Fuchs, Christian; Mosco, Vincent (tripleC – Open Access Journal for a Global Sustainable Information Society)

Towards Marxian Internet Studies - Fuchs, Christian (tripleC – Open Access Journal for a Global Sustainable Information Society)

Google Capitalism - Fuchs, Christian (tripleC – Journal for a Global Sustainable Information Society)

The Political Economy of Privacy on Facebook - Fuchs, Christian (Television & New Media)

Social Networking Sites and Complex Technology Assessment - Fuchs, Christian (E-Politics and Organizational Implications of the Internet: Power, Influence, and Social Change)

Una contribución la crítica de la economía política del capitalismo informacional transnacional - Fuchs, Christian (Nómadas)

Introduction: Internet and Surveillance - Fuchs, Christian; Boersma, Kees; Albrechtslund, Anders; Sandoval, Marisol (Internet and Surveillance. The Challenges of Web 2.0 and Social Media)

Critique of the Political Economy of Web 2.0 Surveillance - Fuchs, Christian (Internet and Surveillance. The Challenges of Web 2.0 and Social Media)

Gesellschaftskritik und Gesellschaftstheorie im Zeitalter des Internets - Fuchs, Christian (Kybernetik, evolutionäre Systemtheorie und Dialektik)

Media, War and Information Technology - Fuchs, Christian (Media & Terrorism. Global Perspectives)

Web 2.0 Surveillance and Art - Fuchs, Christian (Net Works: Case Studies in Web Art and Design)

Some Reflections on Manuel Castells’ Book “Networks of Outrage and Hope. Social Movements in the Internet Age“ - Fuchs, Christian (tripleC - Open Access Journal for a Global Sustainable Information Society)

With or Without Marx? With or Without Capitalism? A Rejoinder to Adam Arvidsson and Eleanor Colleoni - Fuchs, Christian (tripleC - Open Access Journal for a Global Sustainable Information Society)

Conference Report: The 4th ICTs and Society Conference: Critique, Democracy and Philosophy in 21st Century Information Society - Fuchs, Christian (Nordicom Information)

Why social media research matters for Occupy - Fuchs, Christian (Occupy News Network)

Implications of Deep Packet Inspection (DPI) Internet Surveillance for Society. The Privacy & Security-Research Paper Series, edited by Emilio Mordini and Christian Fuchs. Research Paper Number 1. EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action“ - Fuchs, Christian

Photoreduction of Mesoporous In2O3: Mechanistic Model and Utility in Gas Sensing - Wagner, Thorsten; Kohl, Claus-Dieter; Morandi, Sara; Malagù, Cesare; Donato, Nicola; Latino, Mariangela; Neri, Giovanni; Tiemann, Michael (Chemistry - A European Journal)
A model is proposed for the drop in electronic resistance of n-type semiconducting indium oxide (In2O3) upon illumination with light (350 nm, 3.5 eV) as well as for the (light-enhanced) sensitivity of In2O3 to oxidizing gases. Essential features of the model are photoreduction and a rate-limiting oxygen-diffusion step. Ordered, mesoporous In2O3 with a high specific surface area serves as a versatile system for experimental studies. Analytical techniques comprise conductivity measurements under a controlled atmosphere (synthetic air, pure N2) and temperature-resolved in-situ Fourier transform infrared (FTIR) spectroscopy. IR measurements reveal that oxygen vacancies form a donor level 0.18 eV below the conduction band.

Mesoporöse Silica - Moderne Funktionsmaterialien im Chemieunterricht - Wilke, Timm; Haffer, Stefanie; Tiemann, Michael; Waitz, Thomas (CHEMKON)
Poröse Funktionsmaterialien wie halbleitende Metalloxide, Kohlenstoff-Formen oder auch Silica werden aktuell von verschiedenen Wissenschaftsdisziplinen intensiv für Bereiche der Energiespeicherung, Sensorik, Katalyse und Stofftrennung erforscht. Im Beitrag werden schwerpunktmäßig geordnet-mesoporöse Silica-Materialien behandelt, die seit etwa 20 Jahren synthetisch zugänglich sind. Neben den Grundlagen der Herstellung über ein Templat-Verfahren werden im Beitrag auch drei Experimente vorgestellt, die im Chemieunterricht oder Schülerlabor durchgeführt werden können. Zudem wird gezeigt, dass sich verschiedene Aspekte aus dem Kompetenzbereich Fachwissen mit Hilfe des Themas „Mesoporöse Silica“ miteinander vernetzen lassen.

Mesoporous Al2O3 by Nanocasting: Relationship between Crystallinity and Mesoscopic Order - Haffer, Stefanie; Weinberger, Christian; Tiemann, Michael (European Journal of Inorganic Chemistry)
Crystalline, mesoporous alumina (Al2O3) materials with specific surface areas up to 400 m2 g–1 have been synthesized by means of structure replication (nanocasting) using CMK-8 carbon as a structure matrix. A crucial step during this synthesis procedure is the conversion of aluminum nitrate into aluminum hydroxide by treatment with ammonia vapor. The impact of this step was investigated in some detail. Prolonged vapor treatment has a positive impact on the crystallinity of the final Al2O3 products but at the same time leads to loss of mesoscopic structural order and porosity.

Mythisierungen in Vergangenheit und Gegenwart; Dirndl, Diva oder deutsches Mädel in Uniform?; Uniformierung und Uniformherstellung - Kraft, Kerstin

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Mikrosystemtechnik auf Silizium - Hilleringmann, Ulrich

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Theater sucht urbane Umgebung - Laschko, Olga; Novakova, Mina; Shnayien, Marie-Luise; Theile, Mareike (SchauplatzRuhr. Jahrbuch zum Theater im Ruhrgebiet)

Förderungsfall(e). Theater sucht urbane Umgebung - Laschko, Olga; Novakova, Mina; Shnayien, Marie-Luise; Theile, Mareike (SchauplatzRuhr. Jahrbuch zum Theater im Ruhrgebiet)

Psalmenklang. Kuára: Psalms and Folk Songs (Markku Ounaskari / Samuli Mikonen / Per Jörgensen, ECM 2010) - Schroeter-Wittke, Harald (Praktische Theologie)

VOCAbuLarieS - oder: Von der Macht des Wortes im Jahr der Kirchenmusik - Schroeter-Wittke, Harald (Praktische Theologie)

Rhythm Is It! Die Bedeutung des Rhythmus für die Musik der Kirche - Schroeter-Wittke, Harald (Musik und Kirche)

Überlegungen zur Maybe-Education - Schroeter-Wittke, Harald (Kunst und Kirche)

Letzter Sonntag nach Epiphanias. Joh 12,34-36(37-41): Wieso? Weshalb? Warum? Ein Kapitel johanneischer Kinder- und Jugendtheologie - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

16. Sonntag nach Trinitatis. Apostelgeschichte 12,1-11: Der Traum von Freiheit ist Wirklichkeit - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien IV/2)

Engineering high harmonic generation in semiconductors via pulse shaping - Reichelt, Matthias; Hildebrandt, Andre; Walther, Andrea; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XVI)
Paper Abstract High harmonic generation is investigated for a two-band model of a semiconductor nanostructure. Similar to an atomic two-level system, the semiconductor emits high harmonic radiation. We show how one can specifically enhance the emission for a given frequency by applying a non-trivially shaped laser pulse. Therefore, the semiconductor Bloch equations including the interband and additionally the intraband dynamics are solved numerically and the spectral shape of the input pulse is computed via an optimization algorithm. It is demonstrated that desired emission frequencies can be favored even though the overall input power is kept constant. We also suggest special metallic nano geometries to achieve enhanced localized optical fields. They are found by geometric optimization.
Keywords: tet_topic_shg

Tailoring the high-harmonic emission in two-level systems and semiconductors by pulse shaping - Reichelt, Matthias; Walther, Andrea; Meier, Torsten (Journal of the Optical Society of America B)
The generation of specific high harmonics for an optical two-level system is elucidated. The desired emitted radiation can be induced by a carefully designed excitation pulse, which is found by a multiparameter optimization procedure. The presented mechanism can also be applied to semiconductor structures for which the calculations result in much higher emission frequencies. The optimization procedure is either performed using a genetic algorithm or a rigorous mathematical optimization technique.

Musik und Theologie. Ein praktisch-theologischer Literaturbericht - Schroeter-Wittke, Harald (Praktische Theologie)

Data Mining and Decision Making - Meydani, Elnaz; Bahonar, Marziyeh; Gholami, Bahareh; Raeesi Vanani, Iman; Sohrabi, Babak (Advances in Business and Management. Volume 5)

Erfahrungen mit Armut und Gewalt auf dem afrikanischen Kontinent - "Hundert Tage" von Lukas Bärfuß und "Ein Zimmer im Haus des Krieges" von Christoph Peters - Müller, Inez (Armut)

Zeitenwende(n) des Films – Temporale Nonlinearität im zeitgenössischen Erzählkino - Eckel, Julia

Anthropomorphe Audiovisualität – Problematisierung eines Forschungsgegenstands - Eckel, Julia (Revisionen – Relektüren – Perspektiven)

Die Überwindung der Zeit im Fluss der Bilder – Achronologien des Films - Eckel, Julia (Im Moment des ‚Mehr‘ – Mediale Prozesse jenseits des Funktionalen)

Vom Orient über den Nordpol zum ICH – (Des)Orientierende Medien und narrative Irrgärten - Eckel, Julia (Double – Magazin für Puppen-, Figuren- und Objekttheater, 1/2012 (Themenheft „Wo bin ich hingeraten? Räumliche und andere (Des)Orientierungen“))

Vector bundles on degenerations of elliptic curves and Yang-Baxter equations - Burban, Igor; Kreußler, B.

On the Hall algebra of an elliptic curve I - Burban, Igor; Schiffmann, O. (Duke Mathematical Journal)

Semi-stable vector bundles on elliptic curves and the associative Yang-Baxter equation - Burban, Igor; Henrich, T. (Journal of Geometry and Physics)

Two descriptions of the quantum affine algebra Uv(sl2) via Hall algebra approach - Burban, Igor; Schiffmann, O. (Glasgow Journal of Math.)

Frobenius morphism and vector bundles on cycles of projective lines - Burban, Igor (Communications in Algebra)

Singularity category of a non–commutative resolution of singularities - Burban, Igor; Kalck, M. (Advances in Mathematics)

"Total loss of communication". Der Absturz des Space Shuttle Columbia im Live-Fernsehen - Adelmann, Ralf (Fernsehbilder im Ausnahmezustand. Zur Rhetorik des Televisuellen in Krieg und Krise)

"There is no correct way to use the system." Datenbanklogiken und mediale Formen - Adelmann, Ralf (Sortieren, Sammeln, Suchen, Spielen. Die Datenbank als mediale Praxis)

„Bridging the gap“ – Kontextübergreifendes Lernen mit und über Medien - Herzig, Bardo; Martin, A. (Die Zukunft des Lernens – Wie digitale Medien Schule, Aus- und Weiterbildung verändern)

PLAZ – Lehrerbildung in Paderborn - Rinkens, H.-D.; Hilligus, A.; Herzig, Bardo (40 Jahre Universität Paderborn)

Medienbildung. Grundlagen und Anwendungen. Handbuch Medienpädagogik Bd. I - Herzig, Bardo

Raum, Macht und Differenz in gesellschaftlichen Transformationsprozessen: Perspektiven der interkulturellen und vergleichenden Erziehungswissenschaft - Freitag, Christine; Hummrich, Merle; Riegel, C. (Themenheft der Zeitschrift Tertium Comparationis)

„Wenn meine Eltern nachts zanken, kann ich nicht schlafen.“ Kinder als Opfer von Gewalt in der Familie - Freitag, Christine (Schüler. Wissen für Lehrer. Jahresheft zum Thema Gewalt. In: Heidrun Bründel, Christine Freitag, Inge Michels, Wilfried Schubarth, Ludwig Stecher, Klaus-Jürgen Tillmann (Hg.))

Schüler. Wissen für Lehrer (Jahresheft zum Thema Gewalt)

Praxisforschung in der Lehrerbildung. Paderborner Beiträge zur Unterrichtsforschung und Lehrerbildung

Raum, Macht und Differenz in gesellschaftlichen Transformationsprozessen: Perspektiven der interkulturellen und vergleichenden Erziehungswissenschaft (Themenheft der Zeitschrift Tertium Comparationis)

Einleitung: Praxisforschung in der Lehrerbildung - Freitag, Christine (Praxisforschung in der Lehrerbildung)

Raum, Macht und Differenz – Einführung in das Themenheft - Freitag, Christine; Hummrich, Merle; Riegel, C. (Raum, Macht und Differenz in gesellschaftlichen Transformationsprozessen. In: Dies. et al. (Hg.))

„… daß sie mehr als Thier sind, welches man mit dem Stocke schlagen muß.“ Zur langwierigen Abkehr von Schulzucht und -züchtigung - Freitag, Christine (Schüler. Wissen für Lehrer. Jahresheft Gewalt. In: Heidrun Bründel, Christine Freitag, Inge Michels, Wilfried Schubarth, Ludwig Stecher, Klaus-Jürgen Tillmann (Hg.))

Effect of Dispersion on the Structure and Dynamics of the Ionic Liquid 1-Ethyl-3-Methylimidazolium Thiocyanate - Pensado, A. S.; Brehm, Martin; Thar, J.; Seitsonen, A. P.; Kirchner, B. (ChemPhysChem)

Short Time Dynamics of Ionic Liquids in AIMD-Based Power Spectra - Wendler, K.; Brehm, Martin; Malberg, F.; Kirchner, B.; Site, L. Delle (J. Chem. Theory Comput.)

A One-Parameter Quantum Cluster Equilibrium Approach - Brüssel, M.; Perlt, E.; von Domaros, M.; Brehm, Martin; Kirchner, B. (J. Chem. Phys.)

Proton Transfer and Polarity Changes in Ionic Liquid–Water Mixtures: A Perspective on Hydrogen Bonds from ab initio Molecular Dynamics at the Example of 1-Ethyl-3-Methylimidazolium Acetate–Water Mixtures—Part 1 - Brehm, Martin; Weber, H.; Pensado, A. S.; Stark, A.; Kirchner, B. (Phys. Chem. Chem. Phys.)

On the Ideality of Binary Mixtures of Ionic Liquids - Brüssel, M.; Brehm, Martin; Pensado, A. S.; Malberg, F.; Ramzan, M.; Stark, A.; Kirchner, B. (Phys. Chem. Chem. Phys.)

Manufacturing Processes for Combined Forming of Multi-Material Structures Consisting of Sheet Metal and Local CFRP Reinforcements - Schmidt, Hans Christian; Damerow, Ulf; Lauter, Christian; Gorny, Bernhard; Hankeln, Frederik; Homberg, Werner; Tröster, Thomas; Maier, Hans Jürgen; Mahnken, Rolf (Key Engineering Materials)
A new and promising approach to the reduction of greenhouse gas emissions is the use of improved lightweight constructions based on multi-material systems comprising sheet metal with local carbon fibre reinforced plastic (CFRP) reinforcements. The CFRP is used to reinforce highly stressed areas and can be aligned to specific load cases. The locally restricted application of CFRP means that the material costs can be effectively reduced by comparison to parts made entirely of CFRP on account of the expensive production process requiring the use of an autoclave. These parts are thus only used in high-priced products. The production of hybrid CFRP steel structures in a mass production process calls for an efficient production technology. Current research work within the scope of a collaborative research project running at the University of Paderborn is concentrating on the development of manufacturing processes for the efficient production of automotive structural components made up of sheet metal blanks with local CFRP patches. The project is focusing especially on basic research into the production of industrial components. The aim of the investigation is to create an efficient and controlled process for producing CFRP reinforced steel structures from semi-finished hybrid steel-CFRP material. This includes tool concepts and an appropriate process design to permit short process times. The basis of an efficient process design is an in-depth knowledge of the material behaviour, and hence a thorough characterisation was performed. Material parameters were determined for both simulation and forming. For this, monotonic tensile, shear and bending tests were conducted using both uncured prepregs and cured CFRP specimens. To achieve an accurate simulation of the forming process, a special material model for carbon fibre prepregs has been developed which also includes the anisotropic material behaviour resulting from fibre orientation, the viscoelastic behaviour caused by the matrix and the hardening effects that prevail during curing. Recent results show good qualitative agreement and will be presented in this paper. In order to control the properties of the hybrid components, four different tool concepts for the prepreg press technology have been developed and tested. The concepts are presented and the results of experimental investigations are discussed in this paper.

Simulation and manufacturing of deep drawn parts reinforced by carbon fibre prepregs - Gorny, B.; Hankeln, Frederik; Lauter, Christian; Schmidt, H. C.; Damerow, U.; Mahnken, Rolf; Maier, H. J.; Tröster, Thomas; Homberg, Werner

Methodik für die Produktentstehung hybrider Leichtbaustrukturen - Lauter, Christian; Tröster, Thomas; Brandis, Rinje; Gausemeier, Jürgen (Lightweight Design)

Plädoyer für die Klage vor Gott - Tatari, Muna (Islam in der deutschen und türkischen Literatur)

Gott und Befreiung. Befreiungstheologische Konzepte in Islam und Christentum

Die professionelle Kompetenz angehender Physiklehrkräfte in verschiedenen Ausbildungsformen - Riese, Josef; Reinhold, Peter (Zeitschrift für Erziehungswissenschaft)
Keywords: Education

Kompetenzen von Lehramtsstudierenden in Physik - Riese, Josef; Reinhold, Peter (Formate Fachdidaktischer Forschung. Empirische Projekte – historische Analysen – theoretische Grundlegungen)